Systematic Review: The Role of Leadership in Implementing Council Strategic Plans in Tanzanian Local Government Authorities: مراجعة منهجية: دور القيادة في تنفيذ الخطط الاستراتيجية للمجالس في السلطات المحلية التنزانية - Pandisha, Haghai (Journal of North African Economies, 2025)
Strategic plan implementation failures persist in 42% of Tanzanian Local Government Authorities (LGAs), despite decentralization reforms. This systematic review (PRISMA 2020) analyzes 28 studies (2010-2024) to evaluate leadership's role in bridging this gap. Findings reveal transformational leadership (vision-setting, staff empowerment) drives 70-85% target achievement in high-performing councils (e.g., Dodoma, Arusha), while laissez-faire approaches correlate with 20-35% success. Stakeholder engagement (quarterly community forums) and adaptive resource mobilization(PPPs, crisis-redirected funds) emerge as critical practices, boosting outcomes by 72% and 68% respectively. However, contextual barrierssignificantly constrain effectiveness: political interference (30% patronage appointments) and rural capacity gaps reduce impact, while female leaders (15% of directors) achieve 25% higher education/health targets despite sociocultural resistance. The review concludes that leadership is the linchpin of implementation success, but systemic reforms are essential. Key recommendations include: (1) depoliticizing director appointments through independent panels, (2) establishing national leadership academies for transformational skills training, and (3) implementing gender quotas (30%) with mentorship programs. These evidence-based interventions can align Tanzania’s decentralization goals with on-ground development outcomes.